2019
DOI: 10.1186/s41016-019-0165-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolated cerebral aspergillus abscess as a complication of pulmonary alveolar proteinosis in a child

Abstract: Background: Pulmonary alveolar proteinosis (PAP) poses a risk of opportunistic infections with a variety of organisms with Nocardia being the most common pathogen followed by mycobacteria and fungi. Case presentation: A 7-year-old female child, presented with headache and multiple episodes of vomiting. There was no fever or altered sensorium. On examination, there were no focal deficits or cranial nerve palsies. An MRI brain showed a small T2 hyperintense lesion in the left superior parietal lobe suggestive of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…The patient was treated with voriconazole with uneventful follow-up till date. 6 De Villiers De La Noue V et al reported a 20 mm left parietal corticosubcortical cerebral abscess associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Stereotaxic brain biopsy revealed the presence of Aspergillus fumigatus.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was treated with voriconazole with uneventful follow-up till date. 6 De Villiers De La Noue V et al reported a 20 mm left parietal corticosubcortical cerebral abscess associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Stereotaxic brain biopsy revealed the presence of Aspergillus fumigatus.…”
Section: Discussionmentioning
confidence: 99%